2011
DOI: 10.1111/j.1528-1167.2011.03119.x
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms of anxiety and depression in childhood absence epilepsy

Abstract: Childhood absence epilepsy (CAE) has been recently linked to a number of cognitive, behavioral, and emotional disorders. Identification of affective disorders (anxiety and depression) presents unique challenges in pediatric populations, and successful early intervention may significantly improve long-term developmental outcomes. The current study examined the specific anxiety and depression symptoms CAE children experience, and explored the role of disease factors in the severity of their presentation. Forty-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
54
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 18 publications
1
54
0
1
Order By: Relevance
“…As expected, we found that parents reported lower health-related quality of life for children with epilepsy than for healthy children, which is consistent with previous results concerning healthrelated quality of life in children with epilepsy. 9,[22][23][24] In the present study, scores on individual subscales of the health-related quality of life in children with epilepsy were also significantly lower. The sequence of scores from low to high is as follows: social function, cognitive function, general health, behavioral function, physical function, and emotional well-being.…”
Section: Discussionmentioning
confidence: 62%
“…As expected, we found that parents reported lower health-related quality of life for children with epilepsy than for healthy children, which is consistent with previous results concerning healthrelated quality of life in children with epilepsy. 9,[22][23][24] In the present study, scores on individual subscales of the health-related quality of life in children with epilepsy were also significantly lower. The sequence of scores from low to high is as follows: social function, cognitive function, general health, behavioral function, physical function, and emotional well-being.…”
Section: Discussionmentioning
confidence: 62%
“…Children with epilepsy are up to five times more likely to have a depressive or anxiety disorder compared to healthy controls . Furthermore, studies have found that pediatric epilepsy patients’ depressive and anxiety scores on standardized measurements are often within the clinically significant range . As seizure frequency has been associated with increased anxiety and depressive symptoms in pediatric epilepsy, resective epilepsy surgery may lead to improvements in psychological functioning as a result of improvements in seizure control …”
mentioning
confidence: 99%
“…In addition, we have shown previously that GAERS from our colonies in Melbourne exhibit an anxiety‐like behavioral phenotype using the elevated plus maze and open field tests of anxiety (Jones et al., ). Because anxiety disorders are prevalent in pediatric generalized epilepsy patients (Caplan et al., ; Ott et al., , ; Caplan et al, ; Jones et al., ; Caplan et al, ; Vega et al., ), this high‐anxiety phenotype makes GAERS an appropriate model to study the influence of disease‐modifying drugs on behavioral outcomes (Jones & O'Brien, ).…”
mentioning
confidence: 99%